Violent conjunctures in democratic India - Amrita Basu (Cambridge studies in contentious politics, 2015)
"This book is a pioneering study of when and why Hindu nationalists have engaged in discrimination and violence against minorities in contemporary India. Amrita Basu asks why the incidence and severity of violence differs significantly across Indian states, within states, and through time. Contrary to many predictions, the Hindu nationalist Bharatiya Janata Party (BJP) has neither consistently engaged in anti-minority violence nor been compelled by the centrifugal pressures of democracy to become a centrist party. Rather, the national BJP has alternated between moderation and militancy. Hindu nationalist violence has been conjunctural, determined by relations among its own party, social movement organization, and state governments, and on the character of opposition states, parties and movements. This study accords particular importance to the role of social movements in precipitating anti-minority violence. It calls for a broader understanding of social movements and a greater appreciation of their relationship to political parties"--